Elucidação do mecanismo de resistência de raphanus raphanistrum L. W raphanus sativus L. aos herbicidas inibidores da acetolactato sintase (ALS) - Costa, Leandro Oliveira da (2017)
Raphanus raphanistrum L. belongs to the family Brassicaceae, native to southern Europe widely disseminated across regions of temperate and subtropical world. Weed of economic importance in production fields poses threats to areas where wheat is sown for having suspected resistance to the ALS inhibitors. With the objective of confirm the resistance R. raphanistrum herbicide metsulfuron methyl evaluate the existence of cross-resistance and multiple resistance and meet the competitive ability of the weed, we conducted experiments in a greenhouse at the University of Passo Fundo, in the year 2011/12. To confirm the resistance R. raphanistrum metsulfurom methyl herbicide, we conducted experiments in which the treatments consisted of the use of resistant biotypes (biotype R) and susceptible (biotype S) and ten increasing doses of the herbicide. We evaluated control, reduced size and dry matter (DM). Regression was using nonlinear adjustment of the dose response curve. The biotype R was resistant to the herbicide metsulfuron methyl. To evaluate the existence of cross-resistance and multiple resistance, as well as control of the biotype R was held experiment where the treatments consisted of biotype R and biotype S, 12 herbicides (glyphosate, atrazine, bentazone, 2,4-D, sulfometuron methyl + chlorimuron ethyl, chlorimuron ethyl, cloransulam methyl, iodosulfuron, nicossulfuron, imazethapyr, metsulfuron methyl and Imazapic + imazapyr) and untreated control. Evaluated control and DM. The biotype R has cross-resistance to chemical group’s imidazolinones, sulfonylureas and triazolopyrimidines. The biotype R showed no multiple resistance. The herbicide glyphosate, bentazone, atrazine and 2,4-D shown to be effective in the control of biotype R. To assess the competitive ability of the biotypes Rand biotype S in relation to the culture of wheat, were conducted three experiments arranged in replacement series: (1 - wheat with the biotype R; 2 - wheat with the biotype S; and 3 – the biotype R with the biotype S) at the following ratios: 100:0, 75:25, 50:50, 25:75, and 0:100. Analyzed the competitiveness through diagrams applied to replacement and competitiveness indices with evaluation of the dry matter of shoots and area leaf. The biotype R and biotype S demonstrated superior competitive ability of wheat. The competitiveness of the biotype R compared to the biotype S was similar.